(3GdJbQjH hGdJjSjQ deYQaI Sff GdHTjQ GdfPjQ eMeO Udi Gddg Ydjg hSdes - (3YHO Gddg Hf jhSa Hf eMeO Hf Mjhjg GdLhjfj, CHh eMeO,J (B438 (3g` s
(3ChdgG (B:s
(3CeG HYO aEf Yde GdMOjK ef CaVd GdbQH Edi QH GdYGdejf hcja dG jchf hgh HjGf WQjb NjQ GdNdb hCcQe GdChdjf hGdBNQjf s
(3BNQgG (B:s
(3bGd QShd Gddg GdML cd YGe gh GdCbQY Hf MGHS hMOjK s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B146 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B165s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs